The relationship between loneliness and internalizing disorders among young adults: the mediating and moderating role of ego-resilience - Anita Padmanabhanunni; Tyrone B. Pretorius (Frontiers in Psychiatry)
BackgroundThe relationship between loneliness and internalizing disorders has been well established in psychological research. This study aims to build on existing research by exploring how different components of loneliness—isolation, relational connectedness, and collective connectedness—interact with ego-resilience to influence anxiety, depression, and hopelessness.MethodsThe study participants were young adults (n = 337) who completed the University of California-Los Angeles Loneliness Scale, Ego Resilience Scale, Centre for Epidemiological Studies Depression Scale, State-Trait Anxiety Scale, and Beck Hopelessness Scale. A regression-based moderation and mediation analysis was used to investigate the relationships between the components of loneliness, ego-resilience, and internalizing disorders.ResultsThe results of correlational analysis demonstrated that the zero-order correlations between the components of loneliness, isolation, relational connectedness, and collective connectedness, on the one hand, and internalizing disorders, on the other hand, were all significant. Mediation analyses found that ego-resilience partly mediated the relationships between relational connectedness and internalizing disorders, the relationships between collective connectedness and internalizing disorders, and the relationships between isolation and internalizing disorders. Further, moderation analyses found that ego-resilience moderated the relationships between collective connectedness and relational connectedness, respectively, and hopelessness.ConclusionThis study highlights the central role of ego-resilience in mediating the effects of different facets of loneliness on internalizing disorders. Understanding the mediating and moderating role of ego-resilience can inform therapeutic approaches and interventions aimed at reducing the impact of loneliness on mental health.